Investigation of Submerged Friction Stir Welding of Marine-Grade Aluminum Alloy - Kishta, Emad Eldin Mohammed (2014)
A Master of Science thesis in Mechanical Engineering by Emad Eldin Mohammed Kishta entitled, "Investigation of Submerged Friction Stir Welding of Marine-Grade Aluminum Alloy," submitted in January 2014. Thesis advisor is Dr. Basil Darras and thesis co-advisor Dr. Farid Abed. Available are both soft and hard copies of the thesis.